2006
DOI: 10.1017/s0959270906000256
|View full text |Cite
|
Sign up to set email alerts
|

Taxonomy is important in conservation: a preliminary reassessment of Philippine species-level bird taxonomy

Abstract: Alpha taxonomy involves delineation of the basic unit of biology: the species. The concepts by which we define species, however, have been controversial, with several alternatives competing at present, some creating fewer and some more species units, depending on interpretation of species limits. Although it is tempting to assume that species concepts would have little interaction with the geographic foci of species richness and endemism -and some have so argued -this assumption does not withstand careful anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
50
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(52 citation statements)
references
References 38 publications
2
50
0
Order By: Relevance
“…The subspecies Ixos siquijorensis cinereiceps from Tablas Island will likely be split from the nominate form on Siquijor Island because considerable vocal and plumage differences have been noted (Allen, 2006). This result underscores how Philippine bird diversity is currently underestimated (see Peterson, 2006). Further molecular systematic studies on other bird families and with greater island sampling are recommended to better understand the history of avian diversification in this archipelago.…”
Section: Diversification Of Philippine Bulbulsmentioning
confidence: 75%
See 1 more Smart Citation
“…The subspecies Ixos siquijorensis cinereiceps from Tablas Island will likely be split from the nominate form on Siquijor Island because considerable vocal and plumage differences have been noted (Allen, 2006). This result underscores how Philippine bird diversity is currently underestimated (see Peterson, 2006). Further molecular systematic studies on other bird families and with greater island sampling are recommended to better understand the history of avian diversification in this archipelago.…”
Section: Diversification Of Philippine Bulbulsmentioning
confidence: 75%
“…Many of these species include multiple described subspecies and some workers have suggested that some of these races merit recognition as full species (Fishpool and Tobias, 2005;Allen, 2006;Peterson, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Taxonomy has significant implications for conservation (Agapow et al 2004, Mace 2004, Peterson 2006, Pratt 2010, and accurately assessing the species status of range-restricted taxa is particularly important in threatened island ecosystems such as those of the tropical Pacific. Following development of the BSC, Mayr (1945) revised the taxonomy of birds in the region and grouped many island populations into large polytypic species based on the presumption that they would interbreed in sympatry.…”
mentioning
confidence: 99%
“…A relatively large proportion of Philippine forest birds are classified as members of widespread Southeast Asian species when they are better treated as endemic Philippine species (Peterson 2006, Lohman et al 2010. This underestimation of Philippine species endemicity is largely a historical artifact, a hangover from taxonomic and biogeographic thinking of the mid-twentieth century.…”
Section: Taxonomymentioning
confidence: 99%